Human rights as practice: Dalit women securing livelihood entitlements in South India - "Mangubhai, Jayshree P." (New Delhi, 2014)
This book will be of interest to teachers and students of sociology, development studies, subaltern-Dalit studies, political sociology, women's studies, and social movements. It would also have a good regional market in southern India.
Keywords: Human rights